Selective Thyroid Hormone Receptor-Beta (TRβ) Agonists: New Perspectives for the Treatment of Metabolic and Neurodegenerative Disorders - Saponaro, Federica; Sestito, Simona; Runfola, Massimiliano; Rapposelli, Simona; Chiellini, Grazia (Frontiers in Medicine, 2020)
Thyroid hormones (THs) have profound effects on many physiological processes, such as differentiation, growth and metabolism. A lack of thyroid hormones is not compatible with normal health. Most THs effects are mediated by two different thyroid hormone receptor (TR) isoforms, namely TRα and TRβ, with the TRβ isoform known to be responsible for the main beneficial effects of TH on liver and brain function. Consequently, over the past two decades, much effort has been applied in developing thyroid hormone analogues capable of uncoupling beneficial actions on liver (triglyceride and cholesterol lowering) and central nervous system (CNS) (oligodendrocyte proliferation) from deleterious effects on the heart, muscle and bone. Sobetirome (GC-1) and subsequently Eprotirome (KB2115) were the first examples of TRβ selective thyromimetics, with Sobetirome differing from the structure of thyronines because of the absence of halogens, biaryl ether oxygen, and amino-acidic side chain. Even though both thyromimetics showed encouraging actions against hypercholesterolemia, non-alcoholic steatohepatitis (NASH) and in the stimulation of hepatocytes proliferation, they were stopped after Phase 1 and Phase 2-3 clinical trials, respectively. In recent years, advances in molecular and structural biology have facilitated the design of new selective thyroid hormone mimetics that exhibit TR isoform-selective binding, and/or liver- and tissue-selective uptake, with Resmetirom (MGL-3196) and Hep-Direct prodrug VK2809 (MB07811) probably representing two of the most promising lipid lowering agents, currently under phase 2-3 clinical trials. More recently the application of a comprehensive panel of ADME-Toxicity assays enabled the selection of novel thyromimetic IS25 and its prodrug TG68, as very powerful lipid lowering agents both in vitro and in vivo. In addition to dyslipidemia and other liver pathologies, THs analogues could also be of value for the treatment of neurodegenerative diseases, such as multiple sclerosis (MS). Sob-AM2, a CNS- selective prodrug of Sobetirome has been shown to promote significant myelin repair in the brain and spinal cord of mouse demyelinating models and it is rapidly moving into clinical trials in humans. Taken together all these findings support the great potential of selective thyromimetics in targeting several human diseases characterized by altered metabolism, growth or differentiation.